Social interaction in Children’s Museum: The Bangkok family center (Thung Khru) - Damrongsakul, Weeranan (Journal of Language and Culture, 2016)
This paper seeks to demonstrate that the Bangkok Family Center (Thung Khru) located in Thonburi, Bangkok, is a place of social interaction to help children prepare for the adult world with learning in an enjoyable way. The methodologies used included a qualitative research approach, drawing on both primary and secondary sources. The field research covered observation, interviews, questionnaires and photos. It was found that the Bangkok Family Center (Thung Khru) is a place where families can learn together through exhibition sets and activities. For some of the activities, museum staff members have first-hand knowledge of what the audiences like, what their intellectual level is and what kind of activities they will do. This is a role that a museum needs to play in order to provide a learning environment in which families can connect, especially families from different generations who can interact and learn from each other.